Dampak Kebijakan Cadangan Kerugian Penurunan Nilai Dan Pembiayaan Mudharabah Terhadap Kinerja Keuangan Pada PT Bank Aceh Syariah - Ahmad Fauzan Abdullah; Damanhur Damanhur; Ahmad Fauzul Hakim Hasibuan; Devia Vista Fenuraningsih (LPPM, 2023)
The study aims to determine the influence of the Policy on Allowance for Impairment in the Mudharabah Financing value on the Financial Performance of PT Bank Aceh Syariah. This Study Uses Secondary data obtained by viewing the Financial Statements of Bank Syariah. The Data analysis method used is Multiple Linier Regression with the help of Eviews 10. The results Partially Indicate that CKPN Significanly influences the financial performance of PT Bank Aceh Syariah, and Mudharabah financing significanly affects the financial performance of PT Bank Aceh Syariah. Adjusted R Square value of 0.876535 of 0.877 indicate that 87.7% of financial performance is explained and influenced by the independeni variabel CKPN(XI), Mudharabah Financing (X2), and the remaining 12.3% Is influenced by other variables not included in the study